2005
DOI: 10.1080/10473289.2005.10464641
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Study of Thermal Immobilization of Chromium(VI) with Clay

Abstract: Clay that contains kaolinite has been used extensively as a raw material for manufacturing of bricks and china at 900 -1100°C. This study used clay to stabilize the contaminant chromium(VI) [Cr(VI)] through a heating process at 500 -1100°C. X-ray absorption spectroscopic results indicated that the 500 -900°C heating process transformed hazardous Cr(VI) to nontoxic Cr(III); Cr 2 O 3 was the species detected as most abundant. The 1100°C heating process caused the formation of Cr 2 SiO 5 , which was not detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…8 Cr(VI) is thermally reduced to Cr 2 O 3 , which then partially reacts with kaolin and a clay to form amorphous Cr silicate (ie, Cr 2 O 3 ⅐SiO 2 ) as determined via synchrotron radiationbased X-ray absorption spectroscopy (XAS). 4,8 The kaolin and clay reported in the previous studies are organic free and are mined and/or refined for the porcelain-production sector by the manufacturer. The effect of organics on sintering of kaolin and clay was not investigated.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…8 Cr(VI) is thermally reduced to Cr 2 O 3 , which then partially reacts with kaolin and a clay to form amorphous Cr silicate (ie, Cr 2 O 3 ⅐SiO 2 ) as determined via synchrotron radiationbased X-ray absorption spectroscopy (XAS). 4,8 The kaolin and clay reported in the previous studies are organic free and are mined and/or refined for the porcelain-production sector by the manufacturer. The effect of organics on sintering of kaolin and clay was not investigated.…”
Section: Introductionmentioning
confidence: 97%
“…This influence has not been investigated previously. 4,8 Based on the above, this work aims to investigate how the release of LOI from latosol during thermal treatment affects both Cr speciation and sintering of latosol, both of which eventually impact the extent of Cr stabilization. To do so, we accumulate and compare the information, including XAS spectra, surface morphology, surface area, thermogravimetric analyzer/differential scanning calorimeter (TGA/DSC) results, and 13 C-nuclear magnetic resonance (NMR) spectra of Cr-contaminated latosol and LOI-free latosol samples; both samples were heated previously at various temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors describe a similar decrease in Cr leaching at elevated temperatures and several explanations were reported for this. Some suggest that Cr(VI) can be reduced to Cr(III) by more reducing conditions at higher temperatures (Sorensen et al, 2000; Wei et al, 2005). However, their heating conditions differed much from the conditions in this article as they heated their samples in covered crucibles, which promotes reduction owing to lack of oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…For the Cr 2 O 3 containing refractory linings, since the operation conditions and service atmosphere in a given furnace can hardly be changed in practical production, most of the related work have focused on Cr(VI) minimization using some additives at high temperatures. And the results suggested that acidic components such as SiO 2 , TiO 2 , Fe 2 O 3 and P 2 O 5 can effectively suppress the Cr(III) oxidation during thermal treatment of Cr 2 O 3 containing refractories [4,[23][24][25][26][27][28][29]. However, these oxide additives usually result in formation of low melting point phases in the matrix, which would obviously deteriorate the thermo-mechanical properties or slag corrosion resistance of the refractories [30][31][32].…”
Section: Introductionmentioning
confidence: 99%